2017
DOI: 10.1051/sicotj/2017030
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic-assisted retrograde mosaicplasty for an osteochondral defect of the femoral head without performing surgical hip dislocation

Abstract: Osteochondral autograft transplantation (mosaicplasty) for the osteochondral defects of the femoral head is generally performed with safe dislocation of the hip joint. Here, we present a 27-year-old male patient who had a symptomatic osteochondral defect of the femoral head and underwent mosaicplasty applied by hip arthroscopy without surgical hip dislocation. The preoperative radiological evaluation showed a focal osteochondral defect on the weight-bearing surface of the femoral head. With the assistance of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Finally, 16 studies were found to be eligible for inclusion in our review (Figure 1). Fifty-one (51) femoral head mosaicplasty procedures were published in 16 papers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], which included short-, mid-, and long-term (one case) studies ranging from one case to 27 cases (Table 1). The etiology of the osteochondral femoral head defect included 21 trauma, 13 femoroacetabular impingement (FAI), four osteochondritis dissecans (OCD), one chondroblastoma, eight sequelae of Legg-Calve-Perthes disease, and four epiphyseal dysplasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 16 studies were found to be eligible for inclusion in our review (Figure 1). Fifty-one (51) femoral head mosaicplasty procedures were published in 16 papers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], which included short-, mid-, and long-term (one case) studies ranging from one case to 27 cases (Table 1). The etiology of the osteochondral femoral head defect included 21 trauma, 13 femoroacetabular impingement (FAI), four osteochondritis dissecans (OCD), one chondroblastoma, eight sequelae of Legg-Calve-Perthes disease, and four epiphyseal dysplasia.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that non-weight-bearing for six weeks be followed by gradually increasing weight-bearing as tolerated. The mean follow-up was 29.2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) months. The Postel Merle d'Aubigné score improved from the preoperative period to the latest follow-up, from 10.5 (8-13) points to 15.5 (12)(13)(14)(15)(16)(17) points, and the Harris Hip Score increased from 52.8 (35-74) points to 79.5 (65-93) points, respectively [25].…”
Section: Discussionmentioning
confidence: 99%
“…4,[22][23][24][25] Lately, due to patients reluctance to undergo a major surgery, there has been a trend towards developing arthroscopic alternatives, including transtrochanteric drilling and even arthroscopic retrograde osteochondral autologous transplantation. 11,26,27 In this scenario, we intended to report the outcomes of an arthroscopically assisted, percutaneous retrograde drilling of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…With satisfactory outcomes, the historic treatment method described for this pathology has been open surgery, including both surgical hip dislocation and mini-invasive anterior approach 4,22–25. Lately, due to patients reluctance to undergo a major surgery, there has been a trend towards developing arthroscopic alternatives, including transtrochanteric drilling and even arthroscopic retrograde osteochondral autologous transplantation 11,26,27. In this scenario, we intended to report the outcomes of an arthroscopically assisted, percutaneous retrograde drilling of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondral defects may result from trauma, femoro‐acetabular impingement, osteochondritis dissecans, avascular necrosis, or sequalae of Legg–Calvé–Perthes disease [3, 11, 14, 17, 22, 30]. In young patients, different surgical strategies have been proposed to repair chondral lesions and restore articular surfaces, including microfracture, autologous chondrocyte implantation, and osteochondral autograft or allograft transplantation [10, 12, 14, 23, 24, 26, 30].…”
Section: Introductionmentioning
confidence: 99%